Pengaruh CEO Power, Good Corporate Governance, Profitabilitas, dan Ukuran Perusahaan terhadap Pengungkapan Corporate Social Responsibility (CSR) - Sjarief Hidajat; Firzano Triardanaputra Silalahi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of CEO power, good corporate governance projected by the size of the board of commissioners and independent commissioners, as well as profitability, and company size on Corporate Social Responsibility (CSR) disclosure. This research is a quantitative study with multiple linear regression analysis techniques. The population in this study are companies from all sectors listed on the Indonesia Stock Exchange in the period 2020 - 2022. The sampling technique used purposive sampling and resulted in 110 samples so the total research data in accordance with this research period was 330 data. The results showed that CEO power, independent board of commissioners, and company size had no effect on CSR disclosure. Meanwhile, board size and profitability have a positive effect on CSR disclosure. This indicates that the greater the size of the board of commissioners and the profitability of a company, the greater the CSR disclosure.